The Model Implementation Problem Based Learning (PBL) in Social Sciences (IPS) Subjects to Improve Dan's Interests Student Learning Outcomes - Nikmah (Journal of General Education Science, 2024)
Teachers play a central role in shaping the quality of education, and factors such as competence, well-being and work climate are interrelated, forming the basis for the success of the education system. Teacher competency, including pedagogical, personal, social and professional aspects, is identified as the main pillar in creating a conducive work climate. Teacher share public cloud during This understood as person Which his job teach. Shift understanding Teacher from person Which his job teach become professional educators, but for some people it may not be that big of a problem. Teacher own influence Which outside normal for direction development education in Indonesia shift understanding to Teacher from teach become educator Already become legal decisions in Indonesia that have been ratified both regulations regarding Teachers and Lecturers. The law describes teachers as professional educators rather than as people whose job is to teach with the skills of professional staff. Students will be encouraged to learn when they have the motivation to learn. 1) Strong will to do, 2) Amount time Which provided For Study, 3) Willingness leave obligation or task Which other, 4) Perseverance in do task. Grow motivation Study student is Wrong One technique in develop ability And will Study. Wrong One method Which logical For motivation student in learning is hook experience Study with student motivation. Teachers as people who teach students are very interested inthis problem. So as teachers or prospective teachers, we must always try as much as possible to increase learning motivation, especially for students who experience difficulties in learning by using various efforts that can be carried out by the teacher, namely 1) Clarify objective Which want to achieved. 2) Awaken motivation student. 3) Create a pleasant atmosphere for learning. 4) Using a variety of presentation methods interesting. 5) Give reasonable praise for each student's success. 6) Give an assessment. 7) Give comment to results work student. 8) Create competition And cooperation